A proactive approach to prevent non-communicable diseases through screening and educating emergency department attendees to adopt healthy lifestyles: Study protocol for a pragmatic, multicenter, randomized controlled trial - William Ho Cheung Li; Eliza Lai-Yi Wong; Wei Xia; Hong Chen; Sik-Hon Tsui; Yiu Cheung Chan; Kai Yeung Cheung; Yuen Fan Leung; Long Kwan Laurie Ho; Kai Chow Choi; Oi-kwan Joyce Chung (PLoS ONE, 2025)
Noncommunicable diseases (NCDs) have become the leading contributors to morbidity and mortality worldwide, responsible for 74% of all deaths. The major risk factors that substantially contribute to and significantly increase the risk of dying from NCDs include tobacco and alcohol use, unhealthy diet, and physical inactivity. Proactive prevention strategies are vital in reducing the burden. Presenting at the emergency department (ED) can be an excellent “teachable moment” to intervene for unhealthy behaviors because people seeking medical treatment from doctors at EDs may be more motivated to adopt healthy lifestyles. We aim to examine the effectiveness of a general health promotion intervention based on self-determination theory in helping ED attendees adopt a healthy lifestyle. A randomized clinical trial will be conducted on Chinese adults aged ≥18 years attending the EDs of five major acute care hospitals in Hong Kong. Participants will be randomized 1:1 into intervention and control groups (n = 586 per group). Intervention group will receive a brief telephone intervention using the AWARD (Ask, Warn, Advise, Refer and Do-it-again) model, weekly personalized instant messages and four 1-minute videos focused on the desired behaviors via WeChat/WhatsApp, and follow-up assessments of behavior changes at 3, 6, and 12 months. While control group will receive similar brief intervention which only advises them to adopt a healthy lifestyle, similar number of SMS messages containing only general health advice, and follow-up assessments at same schedule with the intervention group. Outcome measures include the composite event rate of adopting at least one of the four healthy lifestyles at 6 (primary outcome) and 12 months measured by a behavioral risk-factor questionnaire and improvement in health-related quality of life at 6 and 12 months measured by the EuroQoL 5-Dimension 5-level (EQ-5D-5L) questionnaire. Ethical approval has been obtained. This trial is registered at ClinicalTrials.gov on March 17, 2025: NCT06889792.